Analysis of land auctions in Ukraine: problems and proposals for improvement - Dorosh, O.; Dorosh, I.; Tarnopolskyi, Ye. (Land Management, Cadastre and Land Monitoring, 2020)
The state of legislative support as a basis for holding land auctions in Ukraine is analysed and the requirements for organizing and holding land auctions for creating, above all, conditions for their conducting on a competitive basis and in accordance with the economic interests of the state are found. In order to remedy the current situation, we collected, systematized and analysed statistical data on the conduct of land auctions during 2017-2019, the level of revenue for the right to lease or sell land, the effectiveness of the auction. It has been found that the purchase and sale of the right to lease land and land themselves through a land auction is a of selling them in the shortest possible time, but not at the best possible price. The not received funds for the right to lease or sell land during the period under review amounts to UAH 746 million 989 thousand, which is primarily indicative of the absence of financially viable buyers among Ukrainians. Against this background, problems with land bidding were identified, and proposals were made to address them.Keywords: land auctions, electronic land auctions, land revenue, bidding performance